2013
DOI: 10.1590/0037-8682-0087-2013
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a diet formulation with oats, soybeans, and flax on lipid profiles and uricemia in patients with AIDS and dyslipidemia

Abstract: Revista da Sociedade Brasileira de Medicina Tropical 46(6):691-697, Nov-Dec, 2013http://dx.doi.org/10.1590/0037-8682-0087-2013 INTRODUCTION ABSTRACT Introduction:Although the initiation of highly active antiretroviral therapy (HAART) is accompanied by an attenuation of viral load, metabolic disorders characterized by hyperglycemia, dyslipidemia, and lipodystrophy are often observed in patients under this treatment. Certain foods, such as oat bran, soy protein, and fl axseed, have been shown to improve a patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
4
0
3
Order By: Relevance
“…Foram incluídos na revisão onze artigos [20][21][22][23][24][25][26][27][28][29][30] . Estes foram publicados entre os anos de 2002 e 2013, sendo cinco estudos realizados nos Estados Unidos 21,23,[27][28][29] e outros três no Brasil 20,22,24 . Além disso, um estudo foi realizado no Canadá 25 , um na Croácia 26 e outro na Europa 30 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Foram incluídos na revisão onze artigos [20][21][22][23][24][25][26][27][28][29][30] . Estes foram publicados entre os anos de 2002 e 2013, sendo cinco estudos realizados nos Estados Unidos 21,23,[27][28][29] e outros três no Brasil 20,22,24 . Além disso, um estudo foi realizado no Canadá 25 , um na Croácia 26 e outro na Europa 30 .…”
Section: Resultsunclassified
“…Os estudos investigaram os resultados das seguintes intervenções dietéticas: um estudo avaliou os efeitos de uma formulação de dietas com farelo de aveia (20g), proteína de soja (10g) e linhaça (10g) na melhora do perfil lipídico 20 ; um estudo analisou a ingestão de cálcio e consumo de grupos alimentares em relação às alterações metabólicas 24 ; um estudo avaliou a suplementação de picolinato de cromo 400 μg/dia na melhora da resistência à insulina e outras anormalidades metabólicas 25 ; dois estudos propuseram analisar a resposta da dieta do mediterrâneo 26,27 , um deles avaliando a associação da aderência à dieta mediterrânea e a dislipidemia durante o primeiro ano de terapia antirretroviral 26 e outro analisando se a aderência à dieta mediterrânea está favoravelmente associada a aspectos metabólicos 27 ; três estudos analisaram a suplementação de ômega-3, um deles utilizou uma dieta baseada nas recomendações da National Cholesterol Education Program (NCEP) mais o suplemento ômega-3 21 ; o segundo utilizou suplementação de um grama duas vezes ao dia, observando seu efeito sobre a função endotelial 23 ; e o último utilizou a dieta recomendada pela American Heart Association somada à orientação de atividade física e suplementação de ômega 3 29 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Thus, because its omega fatty acids are associated with lignins and vitamins, linseed is considered a functional food with potential antiatherogenic effects [35,36]. Kaithwas et al [37] demonstrated that Linum usitatissimum fixed oil possesses anti-inflammatory, analgesic and antipyretic activities.…”
Section: Discussionmentioning
confidence: 99%
“…The author suggested that further studies with higher amounts be performed to assess the effect of this formulation on the lipid profile [62]. The author suggested that further studies with higher amounts be performed to assess the effect of this formulation on the lipid profile [62].…”
Section: Nutritional Intervention On Hiv-related Dyslipidemia: Dietarmentioning
confidence: 99%